Autistic People Do Enhance Their Selves. Issue 5 (July 2020) - Gernsbacher, Morton Ann; Stevenson, Jennifer L.; Dern, Sebastian
We investigated whether autistic people are less prone to self-enhance (i.e., portray themselves in socially desirable ways). Autistic ( N = 130) and non-autistic ( N = 130) participants first responded to social desirability items using the standard instruction to endorse each item as true or false about themselves. Then, all participants read an explanation of what social desirability items measure before responding again to the social desirability items. Self-enhancement was operationalized as participants endorsing more social desirability items before learning the explanation than after. All participants endorsed significantly more social desirability items before learning the explanation than after, F subjects (1, 258) = 57.73, p < .001, η p 2 = .183; F items (1, 34) = 43.04, p < .001, η p 2 = .559). However, autistic and non-autistic participants did not significantly differ in how many items they endorsed, either before or after reading the explanation, indicating that autistic people are as susceptible to social desirability and self-enhancement as non-autistic people are. Our results challenge the claim that autistic people are immune to reputation management.